2005
DOI: 10.1029/2004tc001733
|View full text |Cite
|
Sign up to set email alerts
|

Structural and petrological constraints on the tectonic evolution of the garnet‐lherzolite facies Higashi‐akaishi peridotite body, Sanbagawa belt, SW Japan

Abstract: [1] The Higashi-akaishi peridotite body in the Sanbagawa metamorphic belt is a unique example of a kilometer-scale body including garnet-lherzolite facies rocks from an oceanic subduction-type orogen. In this body, four distinct deformational phases D 1 , D 2 , D 3 , and D 4 can be defined. The tectonic significance of D 1 is unclear. Microstructural observations and application of garnet-orthopyroxene geothermobarometry suggest that D 2 took place during high-temperature subduction up to depths of $100 km (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 69 publications
(132 reference statements)
3
78
0
Order By: Relevance
“…These have been exhumed from the depths of approximately 120 km and originate through dewatering of the subducting slab and subsequent hydration reactions with the host mantle-wedge olivine (Mizukami & Wallis 2005). These inclusions contain atmosphere-derived noble gases in seawater proportions and halogen ratios indistinguishable from marine pore fluids.…”
Section: Support For Subducted 'Air' Noble Gases In the Terrestrial Mmentioning
confidence: 99%
“…These have been exhumed from the depths of approximately 120 km and originate through dewatering of the subducting slab and subsequent hydration reactions with the host mantle-wedge olivine (Mizukami & Wallis 2005). These inclusions contain atmosphere-derived noble gases in seawater proportions and halogen ratios indistinguishable from marine pore fluids.…”
Section: Support For Subducted 'Air' Noble Gases In the Terrestrial Mmentioning
confidence: 99%
“…Speculated subduction-boundary geotherm at about 89 Ma Figs. 2b, 2d Ds Wallis, 1990Hara et al, 1992Wallis et al, 1992;Aoya, 2002;Mizukami and Wallis, 2005;Mori and Wallis, 2010 -3 Wallis and Ar-Ar Itaya and Takasugi, 1988;Takasu and Dallmeyer, 1990;Dallmeyer and Takasu, 1991;Itaya and Fukui, 1994 -91- Kabir and Takasu (2011) (for Seba pelite in SB), Endo and Tsuboi (2013) (for EI) and Weller et al (2015) (for SB and Kotsu). For Ota et al (2004), only P-T estimates obtained from mineral assemblages involving garnet, clinopyroxene and phengite are plotted.…”
Section: Fettes and Desmons 2007mentioning
confidence: 99%
“…Abbreviations of rock-body names other than KT (Kotsu) follow Fig.3. Petrologically derived P-T paths (Mizukami & Wallis (2005) for HA, Endo (2010) and Endo et al (2012) for WI, Aoya et al (2003) and Weller et al (2015) for KT, and Enami (1998) for the Shirataki unit are shown by bold arrows, and those derived using thermal model of Endo et al (2012) by dashed bold arrows. (a) 117-109 Ma.…”
Section: Fettes and Desmons 2007mentioning
confidence: 99%
“…These results imply that in nature, static antigorite serpentinization precedes shear deformation. However, Nozaka (2005) and Mizukami and Wallis (2005) reported the direct formation of foliated antigorite serpentinite from the Happo-one ultramafic complex and the Higashi-Akaishi peridotite body, Japan. There is uncertainty regarding the formation mechanism and the processes that result in the serpentinization of peridotite.…”
Section: Introductionmentioning
confidence: 99%